2022
DOI: 10.1002/acn3.51553
|View full text |Cite
|
Sign up to set email alerts
|

Phospho‐specific plasma p‐tau181 assay detects clinical as well as asymptomatic Alzheimer's disease

Abstract: Objective Plasma phosphorylated‐tau‐181 (p‐tau181) reliably detects clinical Alzheimer's disease (AD) as well as asymptomatic amyloid‐β (Aβ) pathology, but is consistently quantified with assays using antibody AT270, which cross‐reacts with p‐tau175. This study investigates two novel phospho‐specific assays for plasma p‐tau181 and p‐tau231 in clinical and asymptomatic AD. Methods Plasma p‐tau species were quantified with Simoa in 44 AD patients, 40 spouse controls and an independent cohort of 151 cognitively u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…P-tau217 was measured as phosphorylation occupancy at Thr217 using MS assay developed at Washington University (p-tau217 WashU ), 7 Meso Scale Discovery (MSD) immunoassay developed by Lilly Research Laboratories (p-tau217 Lilly ) 10 , 27 and Single molecule arrays (Simoa) immunoassay developed by Janssen Research and Development (p-tau217 Janss ). 19 , 28 , 29 P-tau181 was measured as phosphorylation occupancy at Thr181 using MS-WashU assays (p-tau181 WashU ), 7 MSD immunoassay developed by Lilly Research Laboratories (p-tau181 Lilly ), 8 , 30 Simoa immunoassay developed at the University of Gothenburg (p-tau181 UGOT ), 9 Simoa immunoassay developed by ADx Neurosciences (p-tau181 ADx ), 20 , 31 Lumipulse immunoassay developed by Fujirebio (p-tau181 Fuji ) and Splex immunoassay from MSD (p-tau181 Splex ). P-tau231 was measured using in-house Simoa immunoassay developed at the University of Gothenburg (p-tau231 UGOT ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P-tau217 was measured as phosphorylation occupancy at Thr217 using MS assay developed at Washington University (p-tau217 WashU ), 7 Meso Scale Discovery (MSD) immunoassay developed by Lilly Research Laboratories (p-tau217 Lilly ) 10 , 27 and Single molecule arrays (Simoa) immunoassay developed by Janssen Research and Development (p-tau217 Janss ). 19 , 28 , 29 P-tau181 was measured as phosphorylation occupancy at Thr181 using MS-WashU assays (p-tau181 WashU ), 7 MSD immunoassay developed by Lilly Research Laboratories (p-tau181 Lilly ), 8 , 30 Simoa immunoassay developed at the University of Gothenburg (p-tau181 UGOT ), 9 Simoa immunoassay developed by ADx Neurosciences (p-tau181 ADx ), 20 , 31 Lumipulse immunoassay developed by Fujirebio (p-tau181 Fuji ) and Splex immunoassay from MSD (p-tau181 Splex ). P-tau231 was measured using in-house Simoa immunoassay developed at the University of Gothenburg (p-tau231 UGOT ).…”
Section: Methodsmentioning
confidence: 99%
“…phosphorylation occupancy at Thr181 using MS-WashU assays (p-tau181 WashU ), 7 MSD immunoassay developed by Lilly Research Laboratories (p-tau181 Lilly ), 8,30 Simoa immunoassay developed at the University of Gothenburg (p-tau181 UGOT ), 9 Simoa immunoassay developed by ADx Neurosciences (p-tau181 ADx ), 20,31 Lumipulse immunoassay developed by Fujirebio (p-tau181 Fuji ) and Splex immunoassay from MSD (p-tau181 Splex ). P-tau231 was measured using inhouse Simoa immunoassay developed at the University of Gothenburg (p-tau231 UGOT ).…”
Section: Csf and Plasma Sampling And Analysismentioning
confidence: 99%
“…Plasma tau phosphorylated at threonine 181, 217, or 231 can discriminate clinically diagnosed AD dementia from both other neurodegenerative diseases and cognitively normal individuals. 12 , 13 , 14 , 15 , 16 Additionally, levels of plasma p‐tau181 associated with AD disease severity, predict brain amyloid and tau pathology captured by PET imaging, and predict AD pathology on autopsy. 17 , 18 In cognitively normal and MCI individuals, higher plasma p‐tau181 is associated with progression to dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2018, studies have shown that blood-based measures of phosphorylated-tau (p-tau) correlate with cerebrospinal fluid and PET measures of amyloid and tau neuropathology, and with symptomatic disease progression. 40 - 48 From a diagnostic perspective, measures of p-tau 217 isomers appear to hold the greatest promise. Independent studies support its sensitivity and specificity for AD, 40 , 42 , 43 , 45 while a head-to-head study established superiority of p-tau 217 measured by mass spectrometry for the diagnosis of symptomatic AD over 9 other immunoassays, with near-perfect ability to discriminate participants with AD (area under the curve of 0.95).…”
Section: A Blood-based Revolutionmentioning
confidence: 99%
“…Increases in plasma p-tau 217 levels may precede changes in tau-PET, and even amyloid-PET. 42 , 43 , 46 Thus, elevations in plasma p-tau 217 may mark the earliest stages of “preclinical” or “asymptomatic” AD. Although the ability to identify asymptomatic patients at-risk of developing cognitive impairment offers little-to-no clinical benefit at the present time, the prospect of effective disease-modifying therapies for AD justifies continued research in this area.…”
Section: A Blood-based Revolutionmentioning
confidence: 99%